A comparison of airway interventions and gastrostomy tube placement in infants with Robin sequence. Issue 6 (June 2020) - El Ghoul, K.; Calabrese, C.E.; Koudstaal, M.J.; Resnick, C.M.
Abstract: The purpose of this study was to evaluate feeding impairment following non-operative or operative management of airway obstruction in a large series of infants with Robin sequence (RS) by rate of G-tube placement. A retrospective study was conducted at Boston Children's Hospital including 225 patients (47.1% female) with RS treated between 1976 and 2018. Subjects were grouped by intervention required for successful management of airway obstruction: non-operative only ( n  = 120), tongue–lip adhesion (TLA, n  = 75), mandibular distraction osteogenesis (MDO, n  = 21), or tracheostomy ( n  = 9). The operative group had a higher rate of G-tube placement (58.1%) than the non-operative group (28.3%, P  < 0.0001). Subjects in the TLA and tracheostomy groups had higher odds of G-tube placement than subjects in the MDO group: odds ratio (OR) 5.5 (95% confidence interval (CI) 1.8–17.3, P  = 0.004) and OR 27.0 (95% CI 3.2–293.4, P  = 0.007), respectively. Syndromic patients and those with gastrointestinal anomalies also had higher odds of G-tube placement: OR 3.5 (95% CI 1.7–7.2, P  = 0.001) and OR 5.9 (95% CI 1.6–21.0, P  = 0.007), respectively. Infants with RS who require an airway operation and those with a syndromic diagnosis or gastrointestinal anomalies are more likely to require placement of a G-tube. Of the operative groups, MDO was associated with the lowest G-tube rate, compared to TLA and tracheostomy.